The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0084796
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus garvieae: Where Is It From? A First Approach to Explore the Evolutionary History of This Emerging Pathogen

Abstract: The population structure and diversity of Lactococcus garvieae, an emerging pathogen of increasing clinical significance, was determined at both gene and genome level. Selected lactococcal isolates of various origins were analyzed by a multi locus sequence typing (MLST). This gene-based analysis was compared to genomic characteristics, estimated through the complete genome sequences available in database. The MLST identified two branches containing the majority of the strains and two branches bearing one strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 52 publications
6
43
2
Order By: Relevance
“…Due to improved molecular methodologies, these strains were revealed to originate not only in fish and dairy products, but also in meat products, vegetables, and cereals (29). Along with this spread, L. garvieae has also been identified as a clinical pathogen in patients with infective endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to improved molecular methodologies, these strains were revealed to originate not only in fish and dairy products, but also in meat products, vegetables, and cereals (29). Along with this spread, L. garvieae has also been identified as a clinical pathogen in patients with infective endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Five milliliters of each environmental sample (for the solid compost soil, 5 g was resuspended in 5 ml of sterile water) was added to 5 ml of double-strength GM17 supplemented with 10 mM CaCl 2 and inoculated with 100 l of an overnight culture of an L. garvieae strain. Nineteen representative strains of previously studied L. garvieae (8) were used for lytic phage isolation. The mixtures were incubated overnight at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…These studies also revealed that L. garvieae is related to Lactococcus lactis, a nonpathogenic bacterium used for the manufacture of several fermented dairy products (9). Divergent genomic lineages were observed, with some ecotypes representing evolutionary intermediates between L. lactis and L. garvieae (8). The presence of insertion sequences (ISs) was also highly variable among L. garvieae strains (10).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…However, unlike shotgun sequencing, PICRUSt does not reflect strain diversity such as that which may be observed in numerous bacterial species, including pathobiont strains [46]. It also cannot yet impute viral or eukaryotic organism function.…”
Section: Metagenomics Inferred By Imputing Genetic Functional Capacitmentioning
confidence: 99%